Monday

July 28, 2014

July 28, 2014

Posted by **dan** on Friday, July 9, 2010 at 6:02am.

- math -
**drwls**, Friday, July 9, 2010 at 7:53amx^2 + y^2 -6x + 4y +2 = 0

can be rewritten as the equation of a circle, as follows.

(x-3)^2 + (y+2)^2 -9 -4 +2 = 0

(x-3)^2 + (y+2)^2 = 11

The center of the circle is (3,-2) and the radius is sqrt(11).

The other equation can be rewritten

(x+4)^2 + (y+1)^2 = 22 -17 = 5

Its center is at (-4,-1) and the radius is sqrt5

It looks to me like the two curves never intersect; I don't see how they can meet the definition of orthogonal.

**Related Questions**

Math - Mark each of the following True or False. ___ a. All vectors in an ...

calculus - two curves are orthogonal at a point of intersection of their ...

calculus - if the tangent of two intersecting circles, at their points of ...

Math - Vectors - Prove that vector i,j and k are mutually orthogonal using the ...

Math - I'm doing a bunch of practice finals and I don't know how to approach ...

Linear Algebra, orthogonal - The vector v lies in the subspace of R^3 and is ...

Math - Show that A = [3 2 4 2 0 2 4 2 3] is distinguishable even though one ...

Calculus - Orthogonal Trajectories - Find the orthogonal trajectories of the ...

Math - Determine whether u and v are orthogonal,parallel, or neither. u=-2i+j v=...

Math - Knowing u = (4,0,-3), v = (x,3,2) and that the orthogonal projection of v...